A Classical Interpretation of the Universe Extrapolated from the Fine Structure Constant (α) (Global Journal of Science Frontier Research, 2024)
The Fine Structure Constant (FSC) model of the universe is a conceptual perspective based on a classical method for analyzing the Fine Structure Constant (α). A Python algorithm calculates prime number property sets where the sum of the elements equals the whole number values for α equal to 137 and139. A hybrid coupling of these property sets produces a U{137/139}twin prime metaverse where α =137.036, an almost exact match to the observed value. The FSC Model projects that the Fractional Coupling Constant (α 137 = 0.036)is a more accurate measure of its relative electromagnetic (EM) strength. This same calculation is used to determine the Fractional Coupling Constants (α m ) for the twin prime metaverses (U{2/3}, U{3/5}, U{5/7}through U{197/199}) to estimate their respective electromagnetic forces. The results suggest that this model mirrors our observable universe and offers an abstract landscape into the quantum nature of electromagnetic forces, including Baryonic Matter, Dark Matter, Dark Energy, and a possible variable speed of light.
Keywords: fine structure constant; quantum; matter; dark matter; dark energy; electromagnetic